2014
DOI: 10.1371/journal.pone.0100962
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Origin of GnIH and NPFF in Chordates: Insights from Novel Amphioxus RFamide Peptides

Abstract: Gonadotropin-inhibitory hormone (GnIH) is a newly identified hypothalamic neuropeptide that inhibits pituitary hormone secretion in vertebrates. GnIH has an LPXRFamide (X = L or Q) motif at the C-terminal in representative species of gnathostomes. On the other hand, neuropeptide FF (NPFF), a neuropeptide characterized as a pain-modulatory neuropeptide, in vertebrates has a PQRFamide motif similar to the C-terminal of GnIH, suggesting that GnIH and NPFF have diverged from a common ancestor. Because GnIH and NPF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 49 publications
0
55
0
Order By: Relevance
“…These three mature peptides were identified in lamprey by immunoaffinity purification and mass spectrometry (Table 1). Osugi et al (2014) further searched for an orthologous LPXRFamide peptide precursor gene and mature peptides in amphioxus, one of the most basal chordates (protochordates), to investigate the evolutionary origin of LPXRFamide peptides. An orthologous LPXRFamide peptide precursor genes was identified in amphioxus.…”
Section: Structure Of Gnih Peptidesmentioning
confidence: 99%
“…These three mature peptides were identified in lamprey by immunoaffinity purification and mass spectrometry (Table 1). Osugi et al (2014) further searched for an orthologous LPXRFamide peptide precursor gene and mature peptides in amphioxus, one of the most basal chordates (protochordates), to investigate the evolutionary origin of LPXRFamide peptides. An orthologous LPXRFamide peptide precursor genes was identified in amphioxus.…”
Section: Structure Of Gnih Peptidesmentioning
confidence: 99%
“…To demonstrate this hypothesis, Tsutsui and colleagues further cloned a precursor cDNA of PQRFamide peptide, which encodes three putative PQRFamide peptides in amphioxus (67). Mature forms of these three endogenous amphioxus PQRFamide peptides were identified by immunoaffinity purification as well as mass spectrometry (67) (Table 2).…”
Section: Discovery Of Gnih and Its Conservation In Vertebratesmentioning
confidence: 99%
“…Mature forms of these three endogenous amphioxus PQRFamide peptides were identified by immunoaffinity purification as well as mass spectrometry (67) (Table 2). Phylogenetic analysis suggested that the amphioxus PQRFamide peptide precursor occurred before the divergence of GnIH and NPFF groups in vertebrates (67).…”
Section: Discovery Of Gnih and Its Conservation In Vertebratesmentioning
confidence: 99%
“…Within these groups, GnIH and NPFF, and Kiss1 and Kiss2 are thought to be paralogous (Felip et al, 2009; Lee et al, 2009; Osugi et al, 2012, 2013, 2014; Pasquier et al, 2012). It is of interest to investigate the evolutionary relationship between RF-amide peptide groups, and search the common origin of these RF-amide peptides.…”
Section: Evolutionary Origin Of Gnih and Its Ancestral Structure And mentioning
confidence: 99%
“…Recently we further identified the ancestral form of GnIH in amphioxus, the most basal chordates (Osugi et al, 2014). These studies suggest that the origin of GnIH-like peptides may date back to the time of the emergence of early chordates.…”
Section: Introductionmentioning
confidence: 99%